Left Pulmonary Artery Ligation and Chronic Pulmonary Artery Banding Model for Inducing Right Ventricular—Pulmonary Hypertension in Sheep. Issue 1 (January 2021) - Ukita, Rei; Tipograf, Yuliya; Tumen, Andrew; Donocoff, Rachel; Stokes, John W.; Foley, Neal M.; Talackine, Jennifer; Cardwell, Nancy L.; Rosenzweig, Erika B.; Cook, Keith E.; Bacchetta, Matthew
Abstract : Pulmonary hypertension (PH) is a progressive disease that leads to cardiopulmonary dysfunction and right heart failure from pressure and volume overloading of the right ventricle (RV). Mechanical cardiopulmonary support has theoretical promise as a bridge to organ transplant or destination therapy for these patients. Solving the challenges of mechanical cardiopulmonary support for PH and RV failure requires its testing in a physiologically relevant animal model. Previous PH models in large animals have used pulmonary bead embolization, which elicits unpredictable inflammatory responses and has a high mortality rate. We describe a step-by-step guide for inducing pulmonary hypertension and right ventricular hypertrophy (PH-RVH) in sheep by left pulmonary artery (LPA) ligation combined with progressive main pulmonary artery (MPA) banding. This approach provides a controlled method to regulate RV afterload as tolerated by the animal to achieve PH-RVH, while reducing acute mortality. This animal model can facilitate evaluation of mechanical support devices for PH and RV failure. Abstract : Supplemental Digital Content is available in the text.